A Comprehensive Review of Annual Reports from Community Mental Health Centers in Kansas - Wedel, Amy (My University, 2019)
Growth in the field of mental health care has provoked an evolution of the definitions of mental health and mental illness, as well as a new understanding of infectious disease and their involvement in the development of mental illnesses. Stigmatization and access to care are two primary issues faced by the institutions seeking to provide care for those with mental illness. A subset of these institutions is Community Mental Health Centers (CMHCs), which provide comprehensive public health care to underserved populations throughout the United States. Pawnee Mental Health Services (PMHS) is one of 26 CMHCs in Kansas, based out of Manhattan in Riley County, and serves ten contiguous counties. The project I completed at PMHS was centered around the creation of an annual report. This report summarized the services provided by PMHS, the clientele they serve, and a financial summary for fiscal year 2018. This report was the culmination of work completed in three phases: (1) research of other CMHCs in Kansas, (2) data presentation, and (3) creation of the report in Adobe InDesign. Each phase of the report produced diverse challenges, and the overall project greatly expanded my view of mental health care. A challenge to public health care in Kansas, for example, is insufficient funding which is driven by poor or lacking public health policy. I gathered a more adequate understanding of Medicaid, and how the utilization of all governmental subsidized insurance is a significant barrier to care. Finally, I developed new skills in sectors including design software, such as Adobe InDesign, exemplifying the importance of multidisciplinary skills as the quintessential purpose of field experience.
Keywords: mental health; annual report; community mental health center; public health